“Architectural heritage”: Notion’s media portrait based on the material of Ural regional media - Olga S. Mezenova (Управление культурой)
The research was a continuation of the author's journalistic activities. The author has been researching the issues of working with heritage for a long time, moderating major specialized discussions, promoting an integrative approach to working with cultural heritage objects and old spaces without status. The current study was preceded by publications about the importance of work in the public field, including material on the educational activities of individual relevant departments in Russian regions, about the importance of the economic component of architectural capital and, as a consequence, about the most important task of the work authorities with businesses that voluntarily entered into the topic of cultural heritage objects and their adaptation to modern use. The empirical basis of the study is publications of information portals of regional media, proposed by the search system for the queries “Ekaterinburg Heritage”, “Tyumen Heritage”, “Chelyabinsk Heritage” for the “news” component. Main research method: contextual analysis. Also used are comparative analysis method, purposive sampling method, logical comparison method, quantitative and historical methods. The conducted research made it possible to form a current media portrait of the concept of “heritage” in the three largest Ural cities: Yekaterinburg, Tyumen, Chelyabinsk, to compare the media portrait with the architectural realities of these municipalities, to identify the relationship between the tone, content, professional level and specificity of publications with the features of working with cultural heritage objects in a specific city. The results obtained make it possible not only to assess the current representation of the topic of heritage in regional online media, but also to initiate new discussions about the mechanisms of working with heritage and their role in the modern news agenda of Russian cities.